The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0100-83582011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Alocação de biomassa de Brachiaria subquadripara sob diferentes concentrações de N, P e K

Abstract: RESUMO -O presente trabalho objetivou avaliar a alocação de biomassa em plantas de Brachiaria subquadripara em função de diferentes concentrações de N, P e K em solução nutritiva. O delineamento experimental utilizado foi inteiramente casualizado, com seis repetições, e os tratamentos constituíram-se de cinco níveis de N, P e K (0, 25, 50, 75 e 100% da concentração na solução-base) durante cinco épocas (intervalos de sete dias). A solução-base utilizada refere-se à diluição de 20% da solução nutritiva para cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…In the Barra Bonita hydroelectric power plant reservoir, Domingos et al (2011) reported to have found nitrogen (N total), phosphorus (PO 4 3-), and potassium (K) concentrations in the water of 55,2; 77,5, and 17.2 mg L -1 , respectively. In the present study, the initial growth of B. subquadripara plants increased in agreement with the increasing concentrations of N, P, and K in the nutrients solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Barra Bonita hydroelectric power plant reservoir, Domingos et al (2011) reported to have found nitrogen (N total), phosphorus (PO 4 3-), and potassium (K) concentrations in the water of 55,2; 77,5, and 17.2 mg L -1 , respectively. In the present study, the initial growth of B. subquadripara plants increased in agreement with the increasing concentrations of N, P, and K in the nutrients solution.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics are thought to be responsible for B. subquadripara being capable of suppressing other competitors (Thomaz & Bini, 1998;Domingos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…O balanço de acúmulo de massa seca em folhas e em colmos pode indicar se a competição e o sombreamento aos quais a planta está submetida são aceitáveis, ou não, para a espécie em avaliação (Domingos et al, 2011). Aspiazú et al, (2008) observaram que plantas de capimarroz (Echinochloa crusgalli) acumularam mais massa em colmos que em folhas quando sob alta intensidade de competição, como forma de sobrepassar as plantas do competidor e formar o seu dossel acima das demais plantas.…”
Section: Resultsunclassified